1998
DOI: 10.1095/biolreprod58.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Social, but Not Photoperiodic, Influences on Reproductive Function in Male Peromyscus aztecus 1

Abstract: Nontropical rodents rely on environmental factors to restrict breeding to a specific time of the year. Among these factors, photoperiod appears to be the primary environmental cue used for predicting optimal breeding conditions. The purpose of the present study was to characterize reproductive function, as well as photoperiodic and social responsiveness in male Peromyscus aztecus, which occupy low-latitude, high-altitude habitats. In experiment 1, adult male P. aztecus were individually housed in either long (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
1
16
2
Order By: Relevance
“…Consistent with previous observations (Demas and Nelson, 1998), P. aztecus did not show reproductive suppression in short days. P. eremicus also did not exhibit reproductive suppression in short days, similar to closely related Peromyscus californicus (Nelson et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with previous observations (Demas and Nelson, 1998), P. aztecus did not show reproductive suppression in short days. P. eremicus also did not exhibit reproductive suppression in short days, similar to closely related Peromyscus californicus (Nelson et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that components of male P. aztecus reproduction did not respond to photoperiod, but that males increased testes mass and T when housed with an intact female for 8 days (Demas and Nelson, 1998). In our study, male P. aztecus did not respond to photoperiod and did not show significant responses to social housing.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…It has been hypothesized that the energetic savings attained by seasonal suspension of reproduction liberates energy for immune function, thereby enhancing immune responses in short-day animals (7). Although additional environmental cues (e.g., temperature, food availability, precipitation, and social cues) have also been studied separately or in conjunction with photoperiod manipulation (8,10,20,28), photoperiod generally appears to be the most influential cue for seasonal adaptations.…”
mentioning
confidence: 99%